Optimal CRA reform: Balancing government regulation and market forces - Kenneth H. Thomas (Levy Economics Institute of Bard College, 2002)
At issue in the debate over the renewal of the Community Reinvestment Act (CRA) of 1977 are the various yardsticks regulators use to judge whether individual institutions are meeting the credit and service needs of low- and moderate-income (LMI) communities. Based on careful examination of new CRA data and assessments of comments by selected stakeholders, the author concludes that if the new rules are to succeed, regulators will have to strike a careful balance between various competing interests vying to tip the balance of power in their favor. For example, to offset the effects of a possibly too-close relationship between industry and government agencies, the rules could mandate very explicit and objective measures of institutions' lending performance. To relieve the burden of compliance, the rules could be simplified and pared down to their essentials. And to prevent banks from taking advantage of vulnerable members of LMI communities, rule makers could adopt strong measures against redatory lending.
Keywords: 330; Kreditpolitik; Bankenreform; Bankenpolitik; Bankenaufsicht; Kredit; Niedrigeinkommen; USA